The Developmental Object and Therapeutic Action. Issue 1 (1st January 2020) - Neely, Carla
ABSTRACT: This paper is an effort to further delineate the concept "developmental object, " highlighting the ways the analyst's emotionality contributes to therapeutic action. This capacity on the part of the analyst is vital to the patient's experience of being seen and understood. It considers the meaning to the patient who experiences the analyst's emotional capacity to see him, and its impact on the patient's ability to reveal himself, to alter the way he relates, and to take a further developmental step. The use of the analyst as a developmental object can occur in all analyses but has been linked historically to technique applicable primarily to developmental pathology. It has also suffered by its confusion with the concept "corrective emotional experience." This paper attempts to correct the confusion as well as to clarify the mechanisms by which the analyst as developmental object contributes to structural change. To highlight the unique role of the developmental object in therapeutic action, clinical material is presented contrasting the use of the analyst as developmental object with that of the analyst as transference object. To achieve this goal, the paper draws on psychoanalytic theorists' study of the concept and illustrative clinical examples.